Some Reflections on Wisdom and its Mathematical Formulations - Aneshkumar Maharaj; Abhay Saxena (Urogram Studi Pendidikan Matematika, Universitas IVET, 2023)
This article focuses on recent definitions of the wisdom concept. From each of those western definitions a mathematical formulation is arrived at. Based on that insight two further mathematical formulations are proposed. The first formula which is based on the product of intuition, knowledge and values is then analysed from the perspectives of three eastern philosophers. Our second proposed formulation is based on the concept of an improper integral. This mathematical formulation is based on the following two main assumptions: an individual’s decisions become progressively matured and comprehensive over his or her life-time; his or her wisdom evolves over that time period. Then the proposed improper integral formulation of wisdom is explained in terms of three case studies which focus on the decisions made by great philosophical personalities over their life-times.